MODERN INFORMATION TECHNOLOGIES FOR MODERN LIBRARY - O. M. Drozd; Zh. M. Molchan (Informatika)
The results of upgrading Automated Library Information System BIT-2000u at the Y. KolasCentral Science Library of the National Academy of Sciences of Belarus by means of RFIDtechnologies are considered.